Agricultural pesticide regulatory environment for pollinator protection across geographical regions - Ngoc T. Phan; Ngoc T. Phan; Edwin G. Rajotte; Guy Smagghe; Guy Smagghe; Zong-Xin Ren; David J. Biddinger; David J. Biddinger; Neelendra K. Joshi (Frontiers in Sustainable Food Systems, 2023)
The alarming decline of pollinator populations has raised significant concerns worldwide and prompted the need for effective pesticide risk assessment within the Integrated Pest and Pollinator Management (IPPM) framework. This paper examines the diverse approaches to pollinator protection within the pesticide regulatory environments of the United States (US), the European Union (EU), and selected Asian countries. The US adopts a reactive approach, regulating pesticides only after evidence of harm emerges, while the EU embraces a proactive stance under the precautionary principle. The EU has implemented stringent regulations, including neonicotinoid bans, and conducts coordinated research on pesticide impacts. In contrast, some Asian countries face challenges with inadequate regulations, leading to adverse health and environmental consequences. This article highlights the need for comprehensive pesticide regulations across different regions to safeguard pollinators and mitigate the non-target risks associated with pesticide use.